2016
DOI: 10.1620/tjem.239.127
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Measured with the Cuff Oscillometric Method Is Predictive of Exercise Capacity in Patients with Cardiac Diseases

Abstract: Arterial stiffness is widely used in assessing arteriosclerosis in the background of increased cardiovascular events. Arteriosclerosis also causes reduction in exercise capacity, which is a most important prognostic factor in patients with cardiovascular disease; however, data on the association between arterial stiffness and exercise capacity are limited. Therefore, a simple and noninvasive measurement of arterial stiffness that reflects the central circulation and exercise capacity is needed. The arterial ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…A previous study reported that AVI could be an independent factor for peak VO2 in patients undergoing CR as it is elevated significantly in patients with coronary artery disease compared with patients with non-coronary artery disease while correlating inversely with the peak VO2. 33) In the present study, we used the left ventricular EF to stratify subjects and found that AVI was an independent factor of peak VO2 in the group of patients with pEF. In addition, there was a significant negative correlation between AVI and peak VO2 in the pEF group with CHF at admission.…”
Section: Discussionmentioning
confidence: 68%
“…A previous study reported that AVI could be an independent factor for peak VO2 in patients undergoing CR as it is elevated significantly in patients with coronary artery disease compared with patients with non-coronary artery disease while correlating inversely with the peak VO2. 33) In the present study, we used the left ventricular EF to stratify subjects and found that AVI was an independent factor of peak VO2 in the group of patients with pEF. In addition, there was a significant negative correlation between AVI and peak VO2 in the pEF group with CHF at admission.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have demonstrated that the AVI is associated with the number of cardiovascular risk factors, the Framingham risk score (Sasaki-Nakashima et al 2017) and CAD (Tazawa et al 2016). The predictive value of AVI in ischemic cardiac disease has also been confirmed in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 83%
“…Another study from Saitama Medical University (Akiyama et al 2010) showed that both AVI and API were significantly related to the development of ischemic cardiac disease in patients with type 2 diabetes. Tazawa et al (2016)found that increased AVI was associated with CAD and reduced exercise capacity in patients with cardiac diseases. A more recent study comprising of 252 participants (149 men and 103 women) revealed that API was independently associated with the Framingham risk score (Sasaki-Nakashima et al 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…The AVE-1500 (Shisei Datum, Tokyo, Japan) is a newly developed device that can non-invasively evaluate arterial stiffness and endothelial dysfunction of the central arteries (arterial velocity pulse index [AVI]) and peripheral arteries (arterial pressure volume index [API]) using a cuff-oscillometric technique in a single blood pressure measurement. We previously reported that the AVI and API are significantly correlated but showed different CV implications 6,7) ; conversely, other studies have reported various implications of these indexes for CV risks [8][9][10][11] . Additionally, both the severity of coronary heart disease and complexity of the coronary artery in affected patients are significantly correlated with API 7) .…”
Section: Introductionmentioning
confidence: 79%